The Role of School Counsellors in the National Aboriginal Youth Suicide Prevention Strategy: An Illustration - Merali, Noorfarah (Canadian Journal of Counselling and Psychotherapy, 2017)
Suicide clusters among Aboriginal communities have been attributed to shared family, social, and environmental adversities linked to their history of colonization and residential schooling. Aboriginal leaders often request mental health support from outside their communities to manage these crises. Health Canada’s National Aboriginal Youth Suicide Prevention Strategy outlines evidence-based activities to be implemented by, or in collaboration with, community members. This article situates school counsellors working in schools on or near Aboriginal reserves within Health Canada’s framework, and describes through an illustration how they can create sustainable partnerships with community members to augment the work of external crisis teams.